Empathy: the ability to hear a patient as a professional tool for a physician - E. O. Taratukhin; E. K. Pavlova; Ya. E. Shnaider (Кардиоваскулярная терапия и профилактика)
The article presents the applied aspects of empathy — a tool of psychological counseling. The mechanisms of empathy and empathic understanding are described. Although a physician is not a psychologist and is not required to have all related competencies, it is the physician who has the power to manage the patient’s disease narrative and lead to constructive coping with the disease situation. In cardiology practice, the psychosomatic component has a significant share from stress regulation to modification of behavioral risk factors. The ability to create a favorable emotional environment without being imbued to the extent to waste own resource is a high-level communication skill. Its basic components are empathy and empathic understanding.